2014
DOI: 10.1123/iscj.2013-0005
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of a Parasport Coach and a Life of Learning

Abstract: The complex process of sport coaching is a dynamic and evolving practice that develops over a long period of time. As such, a useful constructivist perspective on lifelong learning is Jarvis’ (2006, 2009) theory of human learning. According to Jarvis, how people learn is at the core of understanding how we can best support educational development. The purpose of the current study is to explore the lifelong learning of one parasport coach who stood out in his feld, and how his coaching practice evolved and deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 24 publications
1
32
0
8
Order By: Relevance
“…Through these types of discussions and the subsequent reflection, the coaches began to both understand and change how they coached their athletes. These types of interactions were a way of learning for coaches, and recent research in parasport coaching suggests that reflection and collaboration with others can be a means of building a coaching practice (Burkett, 2013;Burkett & Mellifont, 2008;McMaster et al, 2012;Taylor et al, 2014). This notion of reflecting while engaging with others lends support to Boud's (2010) questioning of the individualistic view of learning associated with reflection and his suggestion that it is important to also consider a view of 'reflection within the context of settings which necessarily have more of a group or team-based work orientation ' (p. 25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Through these types of discussions and the subsequent reflection, the coaches began to both understand and change how they coached their athletes. These types of interactions were a way of learning for coaches, and recent research in parasport coaching suggests that reflection and collaboration with others can be a means of building a coaching practice (Burkett, 2013;Burkett & Mellifont, 2008;McMaster et al, 2012;Taylor et al, 2014). This notion of reflecting while engaging with others lends support to Boud's (2010) questioning of the individualistic view of learning associated with reflection and his suggestion that it is important to also consider a view of 'reflection within the context of settings which necessarily have more of a group or team-based work orientation ' (p. 25).…”
Section: Discussionmentioning
confidence: 99%
“…As competent coaches and robust coaching systems are the foundation for strong sport programs, it is worthwhile to consider developing a greater understanding of parasport coaching practice. Much of the early research in parasport found that coaches often rely on past coaching experience gained in the able-bodied context and in nonformal and informal learning environments due, in part, to a lack of formal training and resources for parasport (Cregan, Bloom, & Reid, 2007;McMaster, Culver, & Werthner, 2012;Taylor, Werthner, & Culver, 2014). We know from the able-bodied coaching literature that reflective practice in a coach's learning cycle can play an important role in helping a coach develop their coaching practice (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerando o tempo que os treinadores investigados estiveram expostos à GA, é contundente afirmar que o ingresso nessa carreira correspondeu a um processo "natural" 19,38 . Diversos estudos com foco na carreira e no desenvolvimento de treinadores esportivos 8,12,38 evidenciam que há uma forte relação entre as experiências positivas no esporte e a escolha pela carreira de treinador. Segundo Côté et al 39 e Jones, Armour e Potrac 37 , os treinadores interpretam situções e idealizam ações pedagógicas futuras com base em suas experiências prévias.…”
Section: Discussionunclassified
“…Estudos recentes, de abordagem biográfica [7][8][9][10][11] , mostram que as crenças, os valores e os comportamentos, incorporados por meio das experiências ao longo da trajetória de vida, exercem forte influência no ingresso à carreira e na prática como treinador. Conceitualmente, esse processo tem sido entendido como uma trajetória de participação [12][13][14] , em que a aprendizagem está fundamentada na interação e colaboração social em diferentes contextos e situações, ao longo da vida do treinador [15][16][17][18] .…”
Section: Introductionunclassified